Claudin-4-targeted optical imaging detects pancreatic cancer and its precursor lesions. Issue 7 (7th June 2012) - Neesse, Albrecht; Hahnenkamp, Anke; Griesmann, Heidi; Buchholz, Malte; Hahn, Stefan A; Maghnouj, Abdelouahid; Fendrich, Volker; Ring, Janine; Sipos, Bence; Tuveson, David A; Bremer, Christoph; Gress, Thomas M; et al.
Abstract : Objectives: Novel imaging methods based on specific molecular targets to detect both established neoplasms and their precursor lesions are highly desirable in cancer medicine. Previously, we identified claudin-4, an integral constituent of tight junctions, as highly expressed in various gastrointestinal tumours including pancreatic cancer. Here, we investigate the potential of targeting claudin-4 with a naturally occurring ligand to visualise pancreatic cancer and its precursor lesions in vitro and in vivo by near-infrared imaging approaches. Design: A non-toxic C-terminal fragment of the claudin-4 ligand Clostridium perfringens enterotoxin (C-CPE) was labelled with a cyanine dye (Cy5.5). Binding of the optical tracer was analysed on claudin-4 positive and negative cells in vitro, and tumour xenografts in vivo. In addition, two genetically engineered mouse models for pancreatic intraepithelial neoplasia (PanIN) and pancreatic cancer were used for in vivo validation. Optical imaging studies were conducted using 2D planar fluorescence reflectance imaging (FRI) technology and 3D fluorescence-mediated tomography (FMT). Results: In vitro, the peptide-dye conjugate showed high binding affinity to claudin-4 positive CAPAN1 cells, while claudin-4 negative HT1080 cells revealed little or no fluorescence. In vivo, claudin-4 positive tumour xenografts, endogenous pancreatic tumours, hepatic metastases, as well as preinvasive PanIN lesions, were visualised by FRI and FMT up to 48 h after injection showing a significantly higher average of fluorochrome concentration as compared with claudin-4 negative xenografts and normal pancreatic tissue. Conclusions: C-CPE-Cy5.5 combined with novel optical imaging methods enables non-invasive visualisation of claudin-4 positive murine pancreatic tumours and their precursor lesions, representing a promising modality for early diagnostic imaging.